Microneedles loaded with PD-L1 inhibitor and doxorubicin GelMA hydrogel for melanoma immunochemotherapy - Muzhou Teng; Litian Zhang; Yitao Fan; Meimei Fu; Zhijia Li (Materials & Design)
Cutaneous melanoma is a highly aggressive malignancy that is challenging to eradicate completely, even with surgical excision, and frequently leads to recurrence. The disease also shows significant resistance to conventional chemotherapy and mono-immunotherapy, including immune checkpoint inhibitors. The underlying mechanism is attributed to the tumor’s “cold” microenvironment, which causes an imbalance in immune cells, non-immune cells, and microbiota. To improve therapeutic efficacy, we developed a hydrogel incorporating both the PD-L1 inhibitor and doxorubicin, crosslinked into microneedle-shaped patches. Anti-melanoma efficacy was assessed via in vitro and in vivo experiments. Results showed that the dual-drug-loaded hydrogel microneedles effectively suppressed melanoma progression by enhancing immunogenic cell death and intensifying immune activation through PD-L1 signal inhibition. Additionally, antimicrobial peptides were incorporated into the hydrogel to provide antibacterial effects on cutaneous pathogenic microbes and drug-resistant strains, improving post-surgical care. This hydrogel microneedle platform enhances anti-neoplastic agent delivery and offers a novel approach to melanoma immunochemotherapy.